Pengelolaan Anggaran dan Perangkat Daerah Sekretariat DPRD Kota Padang Sidempuan - Haryanti, Nadya; Apriliani, Susi (As-Syirkah: Islamic Economic & Financial Journal, 2023)
This study aims to determine the Effectiveness of Financial Management in the Secretariat Office of the Padang Sidimpuan District Representative Office which is carried out by the Administration and Secretariat Section of the Financial Management Subdivision regarding Financial Management Effectiveness which includes Budget Planning, Budget Implementation, Budget Reporting and Budgeting. This research uses the method of Financial Management. qualitative. The research informants consisted of the Secretary of the Regional House of Representatives, the Head of Administration and Secretariat, the Head of Sub-Planning and Finance, the Spending Treasurer, and the Planning and Finance Section Staff with a total of 5 informants, the data source consisted of primary and secondary data obtained from collection techniques. data by observing, interviewing, and documenting. The results of the study show that the effectiveness of financial management at the Secretariat of the Regional Representative Council of Padang Sidimpuan Regency is quite good and systematic. improvement of facilities and infrastructure so that tasks can be achieved.